PERAN POLA ASUH STRICT PARENTS DALAM PEMBENTUKAN PERILAKU MAHASISWA PENDIDIKAN SOSIOLOGI UNIVERSITAS SULTAN AGENG TIRTAYASA - Nadia Nurfadila Ramadhani; Dema Tesniyadi (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
Family plays an important role as a foundation for shaping children’s character, attitudes, and intelligence. Parenting patterns, especially authoritarian or known as “strict parents”, have a major influence on children’s mental and social development. Although it can create obedient and high-achieving children, this parenting pattern also has the potential to cause psychological stress, anxiety, and inhibit social skills and self-confidence. This study aims to understand and examine how strict parenting patterns affect the behavioral development of Sociology Education students at Sultan Ageng Tirtayasa University, and to highlight the importance of a balanced parenting approach between discipline and emotional support. The method used in this study is qualitative with a descriptive case study type. Data collection was carried out through interviews and observations. Based on the results of the study, strict parenting patterns can produce someone who is disciplined and responsible with the ability to face academic and social challenges. However, this parenting pattern also causes difficulties in independent decision-making, anxiety, and lack of social skills.